Practical heat treating : basic principles - Dossett, Jon L. (ASM International, 2020)
This book describes the basic principles of heat-treating technology in clear, concise, and practical terms for students, emerging professionals, production personnel, and manufacturing or design engineers.
Keywords: Metals -- Heat treatment.; Steel -- Heat treatment.; Stainless steel -- Heat treatment.; Cast-iron -- Heat treatment.; Nonferrous alloys -- Heat treatment.; elektronické knihy; electronic books